Dichotomic problem of dynamic programming for the strictly convex functions, II - Bistrickas, V. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Б. Бистрицкас. Дихотомическая задача динамического программирования для строго выпуклых функций. II V. Bistrickas. Dichotominis dinaminio programavimo uždavinys griežtai iškiloms funkcijoms. II